Factors influencing Indonesian rural banks' credit disbursement - Setia Murningsih; Muhammad Firdaus; Budi Purwanto (University of Merdeka Malang, 2020)
Distribution of microcredits has a great opportunity, considering micro-businesses in Indonesia reaches 98 percent of all types of businesses. Microlending has become the leading market share for BPRs to channel their funds. This research aims to identify factors that effect the increase of micro-credit disbursements. This study uses a Vector Error Correction Model (VECM) method with a type of monthly time series data from 2012 to 2018. The sample of this study is the Rural Credit Banks. The results of this study explain that the BPR non-performing loan (NPL) variable, both in the long term and short term, does not significantly influence the increase in micro-credit distribution. In contrast, the variable spread in the short term and long term shows a significant positive effect on increasing microcredit distribution. Forecasting for variable increases in credit distribution fluctuates with a downward trend. The NPL variable has an increasing trend, and it is projected that the next 90 months will reach 12 percent. The spread variable has a downward trend for the next 40 months which then the trend will continue to increase for the next 90 months. JEL Classification: D13, I31, J22 How to Cite:Murningsih, S., Firdaus, M., Purwanto, B. (2020). Factors influencing Indonesian rural banks’ credit disbursement. Jurnal Keuangan dan Perbankan, 24(2),189-201.DOI: https://doi.org/10.26905/jkdp.v24i2.3778